Assessment of Radionuclide Activity (238U, 232Th, 40K) in Airborne Dust from Dust Storms in Wasit and Al-Qadissiya, Iraq - Mohammad Yahya R Al-Yasiri; Abdullah Ahmed Khalaf; Hadi D. Alattabi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Dust storms are recurrent environmental events in dry and semi-arid regions and can transport fine particles containing naturally occurring radioactive materials with potential implications for human health. Specific Background: This study assessed uranium-238 (238U), thorium-232 (232Th), and potassium-40 (40K) in samples collected during active dust storms from five sites in Wasit Governorate and one site in Al-Qadissiya Governorate, Iraq, using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Knowledge Gap: Site-specific assessment is required because radionuclide concentrations can differ according to soil type, storm intensity, and source location. Aims: The study measured 238U, 232Th, and 40K activity concentrations, evaluated possible radiological health risks, and compared the findings with published research and international standards. Results: Activity concentrations varied among locations: 238U ranged from 12.1 to 113.5 Bq/kg, 232Th from non-detectable levels to 1.58 Bq/kg, and 40K from 1125.9 to 3546.9 Bq/kg. Sample E005 from Al-Qadissiya recorded the highest 238U and 40K concentrations, while 232Th was not detected in B002 and C003. The measured levels remained below international safety limits. Novelty: The study provides a site-specific comparison of three radionuclides across storm-derived samples from Wasit and Al-Qadissiya using ICP-OES. Implications: The findings support continued environmental monitoring, health-risk assessment, and mitigation measures including afforestation, soil stabilization, and public education. Highlights: The radiation level in of the dust in the air show noticeable geographic difference across Iraqi governorates. The dust sample that examined in the Al-Qadissiya hit high point of the concentrations of uranium-238 and potassium-40. The Measured of the radiation levels remain perfectly safe by global standards Keywords : Dust Storms, Iraq, Radionuclides, 238U, 232Th, 40K, ICP-OES, Radiological Health Risks.